Analysis of Rainfall Rate by a Doppler Radar Image - Arwatchananukul, Sujitra; Phaiboonnimit, Panipa (Asian Health, Science and Technology Reports, 2011)
In Thailand, Royal rain radar is an effective tool to measure and monitor rain continuously. In addition, it is useful for planning, evaluation, and flood warning. Therefore, the propose of this paper is to analyses rainfall rate systematically by a Doppler radar image based on digital image process. This system uses 646x644 pixel-GIF image as an input for finding all considered clouds. Then, it classifies dBz reflective signal levels by using ZR relationship, Z = 300R 1.4 , to calculate the average rainfall rate. According to the rainfall testing data in 15 days with 200 Doppler radar images compared to data of 20 rain gauges at a random period. It is found that the error of calculated rainfall is 36.82 % on the total average deviation.